ARTIFICIAL INTELLIGENCE AS A MEANS OF DEVELOPING PRE-SERVICE MATHEMATICS TEACHERS’ CRITICAL THINKING - Lukashova Tetіana; Drushlyak, Marina (Physical and Mathematical Education, 2023)
Formulation of the problem. Today, education focuses not only on the acquisition of hard skills (knowledge, abilities, skills in a certain subject area) by graduates but on the acquisition of so-called soft skills, i.e., the qualities of the future that a future competitive specialist must have, among which the skills of critical thinking. An urgent issue in the professional education system of pre-service mathematics teachers is the search for proof of the effectiveness of developing critical thinking. Materials and methods. Methods of the theoretical level of scientific knowledge were used to achieve the goal: analysis of scientific literature, synthesis, formalization of scientific sources, description, comparison, and generalization of own experience. Results. The foreign experience of using artificial intelligence in the educational sphere is analyzed. The positive and negative aspects of such use are highlighted. The possibilities of using artificial intelligence for the development of critical thinking of future mathematics teachers are considered using the example of ChartGPT. When studying the topic "Proofing Inequalities," a variant of tasks for students is offered. In completing tasks, ChartGPT is used as a "simulator" for future teachers in working with students. Students are required to evaluate the solutions offered by ChartGPT critically. AI provides several ways to prove the inequalities. However, it makes mistakes in the solutions. The reactions of artificial intelligence to pointing out its errors are presented. Conclusions. The introduction of artificial intelligence into the educational process and its use as a means of developing the critical thinking of future mathematics teachers is considered appropriate. The effectiveness of such an implementation is shown in the example of studying the topic "Proofing Inequalities".